Modlitwa w ujęciu bł. Jana Pawła II - Chmielewski, Marek (Verbum vitae, 2012)
Pope John Paul II devotes such a lot of attention to matter of prayer that is why this article is an outline of this problem. To understanding of prayer the Pope puts the accent on her personal-Christological dimension. It’s indispensable element of sanctification’s process and fundamental symptom of “general spirituality needs” (NMI 33). Christian prayer should draw from wealth of God’s Word. Although it is duty every Christian especially priests and persons of particularly consecration are obligated to pray. They should also be the teachers of prayer. Each one of the states of life in Church has his own specificity of prayer and the last part of article has talked it through. The Pope’s preferred and commended prayers are: the rosary, the Angel of the Lord and the Liturgy of the Hours.